Examining Work Re-Entry Decisions for Single Mothers through Bourdieu’s Capital Theory/Ida Fatimawati Adi Badiozaman ... [et al.] - Voon, Mung Ling; Birdthistle, Naomi; Adi Badiozaman, Ida Fatimawati (Universiti Teknologi MARA Cawangan Sarawak, 2021)
This paper presents the qualitative results of a larger mixed-methods study on how barriers to, and determinants of, the labour market shape re-entry decisions and the role of economic/cultural/social determinants in influencing employment re-entry decisions for single mothers residing in urban Sarawak. Through the lens of Bourdieu’s capital theory, the study examined the decision-making process of single mothers and provided nuanced insights into the factors that enable or impede access to necessary resources for re-entry to work. Data were collected from in-depth semistructured interviews with 26 single mothers in urban Sarawak. The findings revealed that cultural (education), economic (finance), and social (family) capitals were both enabling and impeding factors and were inextricably linked in shaping employment re-entry decisions. Low volumes of these capitals perpetuated the poverty cycle for a majority of these single mothers. The findings reinforced the complexity of integrating single mothers, who have low incomes and low education levels, into employment. Nevertheless, poverty among single mothers and their children can be substantially limited through the right mix of social, education and labour market policies. The study highlights the challenges facing single mothers in urban areas in developing countries, which are quite different from rural areas or developed countries.